Rice residues can be converted to functional health nutrients through mushroom (Pleurotus ostreatus Jacq. ex Fr.) Kummer production - Tang, Erasmus Nchuaji; Ngome, Francis Ajebesone; Ndindengc, Sali Atanga; Bigoga, Jude Daiga; Suh, Christopher; Moreira, Jean (Agriculture and Natural Resources, 2019)
Pleurotus ostreatus (mushroom) growth was investigated on six combinations of rice residues as substrate. The substrate composition and functional health nutrients of slowly dried mushrooms were also analyzed. Substrate formulae respectively composed of rice husk, rice bran (as supplement), and rice straw were designated as SI (625 g, 112.5 g, 350 g), SII (250 g, 112.5 g, 275 g) SIII (847.98 g, 134.80 g, 230.40 g), SIV (402.02 g, 134.80 g, 230.40 g), SV (847.98 g, 90.20 g, 230.40 g) and SVI (402.02 g, 90.20 g, 230.40 g). Effective yield response was observed in SI (58.82% husk, 10.59% bran and 30.59% straw) and SII (39.23% husk, 17.65% bran and 43.14% straw) at pH 7.01 and pH 7.12 (p < 0.05), respectively, and a carbon-to-nitrogen ratio of 60.47 and 60.82, respectively. Biological efficiency and total dry yield, respectively, peaked in SII (67.31%, 66.92 g) and SI (52.29%, 54.94 g). Protein expression was in the range 42.12–65.48 μg/mL and the total phenolic content expressed in milligram equivalents of gallic acid per gram dry weight of mushroom was high in all substrates: SI (186.33), SII (31.91), SIII (121.52), SIV (48.00), SV (44.15) and SVI (87.24); there were selenium traces in SI, SII and SIII. This study revealed that rice residues in adequate proportions are suitable Pleurotus ostreatus substrates in terms of yield and functional health nutrients.